Mortality due to Covid-19 in Brazil: sociodemographic profile of the first weeks (Research, Society and Development, 2021)
On February 26, 2020, the Ministry of Health confirmed the first case of death by Covid-19 in Brazil. This study aimed to identify mortality from the disease in Brazil in the first 6 weeks after confirmation of the first case of death and to outline the profile of these individuals. This is a retrospective, descriptive cross-sectional study, which used data from the daily bulletins of the Ministry of Health. All cases of deaths occurred in Brazil by Covid-19, from March 17 to April 26, 2020, were analyzed. Data from all states of the federation were included and characterized by sex, age, skin color and presence of associated comorbidity. Among the deaths, 72% were from people over 60 years old, although about 80% of those infected did not belong to this age group. Still, 60% were male, even with an average of only 51.4% of infected males. The frequency of deaths was significantly higher among white individuals compared to brown and black individuals (p